Can Coffee Certification Reduce Poverty? Results from a Household Study of Smallholder Farmers in Indonesia - Esther Sri Astuti Soeryaningrum Agustin; Astrid Offermans (Sustainability Science and Resources, 2022)
Sustainability certification are increasingly demanded in the global coffee trade, but its economic and poverty alleviation effects for smallholder farmers are still poorly understood. We study these effects using cross-sectional household data obtained from a survey of 320 farm households from four districts in the coffee-producing provinces of Lampung and Aceh in Indonesia. We combine a monetary expenditure approach with a non-monetary approach. Both approaches reveal information on the number of respondents that can be considered poor, as well as on the intensity of poverty experienced by them. In terms of non-monetary approach, we refer to multidimensional poverty index (MPI) that identifies deprivations in education, health and standards of living. In terms of monetary approach, we examine poverty gap index that measure coffee farmers’ expenditure lies below the poverty line. We compare between certified and conventional (non-certified) coffee farmers. The results show that economic benefits contributing to poverty alleviation can be gained from coffee certification. The differences in the value of poverty measurements between certified and conventional farmers are small but statistically significant. Certified farmers are found to be less frequently poor compared to conventional farmers. There is no significant difference on the intensity of poverty for both groups of smallholder farmers. Given these results, certification is not a highly recommended strategy for poverty alleviation among smallholder coffee farmers in Indonesia.